2009
DOI: 10.1111/j.1365-3059.2009.02064.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of host plant resistance and geographic distance to the structure of Potato virus Y (PVY) populations in pepper in northern Tunisia

Abstract: The genetic structure of Potato virus Y (PVY) populations was investigated in naturally-infected pepper ( Capsicum annuum ) fields, collected at eight different localities in northern Tunisia, where 23% of the sampled plants were homozygous for the pvr2 1 recessive resistance allele, while the other plants carried the dominant susceptibility alleleRestriction fragment length polymorphism analysis at three PVY genome segments revealed a high level of viral diversity, with a majority of cases showing co-infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…The results indicated that geographic region had significant influence on the populations' genetic diversity. These results correspond with the report of Bergmann et al that large differences among geographic isolates of duckweeds were found when they selected superior duckweed (Lemnaceae) genotypes for the utilization of nutrients in animal wastes [32], and the geographic differentiation of some other plants [33][34][35][36]. Different communities may have resulted in the significant genetic differentiation between duckweed populations; local selective forces may greatly affect genetic diversity within duckweed populations.…”
Section: Geographic Differentiation Of Duckweedsupporting
confidence: 89%
“…The results indicated that geographic region had significant influence on the populations' genetic diversity. These results correspond with the report of Bergmann et al that large differences among geographic isolates of duckweeds were found when they selected superior duckweed (Lemnaceae) genotypes for the utilization of nutrients in animal wastes [32], and the geographic differentiation of some other plants [33][34][35][36]. Different communities may have resulted in the significant genetic differentiation between duckweed populations; local selective forces may greatly affect genetic diversity within duckweed populations.…”
Section: Geographic Differentiation Of Duckweedsupporting
confidence: 89%
“…Moreover, genetic drift due to strong bottlenecks during both CMV movement within the plant (Ali & Roossinck, ) and aphid transmission (Ali et al ., ; Betancourt et al ., ) could also favour genetic differentiation between CMV populations. Similar conclusions were drawn for PVY populations in peppers in Tunisia (Ben Khalifa et al ., ), a virus submitted to similar strong bottlenecks (Moury et al ., ; Fabre et al ., ).…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, this unexpected result was confirmed for the samples collected in 2009 (Table ). Total RNAs previously purified from fruits of naturally infected peppers collected in 2006 for the study of Tunisian PVY populations (Ben Khalifa et al ., ) were then analysed. The situation was similar for samples collected in 2006.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations